Trans-cultural nature of Islamic art - Zekrgoo, Amir Hossein (International Institute of Islamic Thought and Civilization (ISTAC), 2009)
Introductory remarks: A thorough understanding of any civilization will be incomplete without the appreciation of its arts, for art is not merely a trend - among other trends - in life, but a manifestation of cultural identity in its diverse totality. It is an embodiment of the faith that governs it, the socio-cultural conditions that give birth to it, the historical grounds that mold it, and the aesthetic values of the people who create it. Studying, in depth, of the arts of a certain civilization is like reliving history: the realm of art is a multi-dimensional source of knowledge that not only involves our intellectual faculty, but touch our souls, engage our emotions and eventually provide a unique timeless experience that transcends the physical boundaries and unites us with the peoples that created them.